Situation Report: Romania, 16 February 1978 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania Introduces the Profit-Sharing System Historical Polemic with Political Implications: Dacian-Romanian Continuity Romanian-Soviet Contacts Stepped Up: How Much Substance? Bulgarian Foreign Minister Visits Romania Angolan Premier Visits Romania Romania's Foreign Trade in 1976 Deficiencies in Agriculture Once Again in the Limelight